Intellectual Property Rights in China - Devonshire-Ellis, Chris; Scott, Andy; Wollard, Sam (China Briefing, The Practical Application of China Business, 2011)
This Guide is a detailed overview of all aspects of IPR and protection in China. Produced in association with AWS, the Austrian Federal Bank?s specialist IPR unit based in Shanghai, this is an essential work for any businessman trading with or conducting business in China. From covering protocol for dealing with Trade Fairs, to the application processes for trademarks, patents, copyright and licensing, as well as dealing with infringements and enforcement,this guide is a practical reference for any businessman with concerned with their IPR in China.